Pengaruh Culturally Responsive Teaching Terhadap Partisipasi dan Motivasi Siswa dalam Pembelajaran IPAS Kelas V SDN 060812 Medan - Nawa, Khairun; Sirait, Dahlia; Yarshal, Dinda; Erlinda, Erlinda; Siregar, Nur Salimah (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of culturally responsive teaching on student participation and motivation in Social Science and Natural Science (IPAS) learning in fifth-grade students at SDN 060812 Medan. This study is a Classroom Action Research (CAR) with 20 fifth-grade students as the subjects. The Minimum Completeness Criteria (KKM) for individual students in IPAS is 75, while the KKM for the class is 80%. Data were collected through student activity observation sheets, motivation questionnaires, and test results. Data analysis was performed using percentage techniques. The results of the study show a significant increase in student participation and motivation. In the first cycle, student participation reached 68.50% (good category), while student motivation was 70.25% (good category). In the second cycle, participation increased to 74.00% (good category), and student motivation reached 76.50% (good category). In the third cycle, a more significant improvement was observed, with student participation reaching 85.50% (very good category), and student motivation reaching 88.00% (very good category). Therefore, the implementation of culturally responsive teaching was proven effective in improving student participation and motivation in IPAS learning in fifth grade student at SDN 060812 Medan